Bibliometric Analysis of Public Expenditure - Loso Judijanto (West Science Accounting and Finance, 2026)
Public expenditure has become an important research area due to its critical role in supporting economic development, improving public services, and addressing societal challenges, particularly in the healthcare sector. This study aims to examine the development, intellectual structure, collaboration patterns, and emerging research trends in public expenditure literature using a bibliometric analysis approach. Scientific publications were collected from a relevant academic database and analyzed using VOSviewer to perform keyword co-occurrence analysis, citation analysis, co-authorship analysis, institutional collaboration analysis, country collaboration mapping, and density visualization. The findings indicate that public expenditure research is primarily concentrated on themes related to health expenditures, public health, healthcare financing, government spending, health policy, and healthcare services. Citation analysis reveals that highly influential studies mainly focus on global health challenges, disease burden, healthcare costs, and the effectiveness of public health interventions. The collaboration analysis demonstrates that the United States plays a central role in global research networks, followed by contributions from China, European countries, and developing nations. Furthermore, the thematic evolution indicates a shift from conventional discussions of healthcare costs toward broader issues involving fiscal governance, policy effectiveness, resource allocation, and sustainable public financing. This study contributes by providing a comprehensive mapping of the current research landscape and identifying future research opportunities related to efficient public resource management, interdisciplinary collaboration, and sustainable expenditure policies.